Exploring the Use of AI-Enhanced Listening Comprehension Tools by EFL Students in the English Department at Universitas Bhinneka PGRI - Moh. Choirul Huda; Nia Roistika; Caterina Nova Triani (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The rapid growth of Artificial Intelligence (AI) in education has introduced new opportunities for improving English listening comprehension, a skill many EFL learners continue to find challenging. This study explores the use of AI-enhanced listening tools among students in the English Department at Universitas Bhinneka PGRI. The research aims to identify the AI tools commonly used by students, examine their perceptions of usefulness, ease of use, and engagement, and investigate the difficulties they encounter when using these tools. A qualitative descriptive exploratory design was employed, combining a questionnaire distributed to 43 students with semi-structured interviews conducted with 10 participants. Data were analyzed using the Miles and Huberman framework, which includes data reduction, data display, and conclusion drawing. The findings indicate that YouTube Auto-Caption is the most widely used AI tool, followed by ELSA Speak and Duolingo, mainly due to their accessibility and familiar interfaces. Students reported positive perceptions of AI-enhanced listening tools, noting that features such as automatic captions, speed control, replay functions, and pronunciation feedback helped them better understand spoken English and increased their motivation to practice listening. Despite these advantages, several challenges emerged, including inaccurate captions, unstable internet connections, limited free features, and insufficient guidance on how to use the tools effectively.Overall, the study concludes that AI-enhanced tools have strong potential to support EFL learners’ listening development, but their effectiveness depends on both technological quality and pedagogical support. The findings highlight the need for teachers to provide structured guidance and for developers to improve usability and accessibility. Future research may examine the long-term impact of AI tools or compare the effectiveness of different platforms in various learning contexts.